Lung Cancer and Smoking in Asia (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
The incidence of lung cancer is rising dramatically in Asia. Cancer is currently placed 6th to 9th in the common causes of mortality in the SAARC region. The most common cancers in Asia are the cancers of head, neck and thorax, which can be directly attributed to the smoking and tobacco chewing habits in the region especially SAARC region. The pattern of cigarette smoking changed globally during last three decade. It is slowly decreasing in developed countries, at a rate of 1% annually and rising in developing countries, at a rate of 2%. Recent studies have shown in addition to the direct tobacco smoking, environmental tobacco smoke has a proven lung carcinogenic effect. As the single most important cause for lung cancer is tobacco smoke, every effort should be taken to control this menace.Key Words: Lung cancer; Asia; Tobacco Smoking DOI: 10.3126/saarctb.v5i1.3082 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(1) 33-38